Analysis of Parents' Needs for Guidelines in Training Communication Skills for Autist Children at Home - Wulan Utami (Journal of Disability, 2021)
The background of this research is that parents of autistic children have difficulty in handling and continuing the communication learning program from school. Many parents feel they do not have special guidelines in practicing communicating with autistic children at home. This study aims to determine the needs of parents for a guide to practice communicating at home. The research approach uses a quantitative-qualitative approach. The subjects in this study were 93 parents of autistic children in several special schools in Central Java. The data collection technique used a questionnaire instrument totaling 15 statement items. The questionnaire in this study used a Likert scale with 4 alternative answers, namely very need, need, need less, and don't need. The data analysis technique in this study used a descriptive analysis approach through SPSS 26 software. After the data was analyzed, the data were interpreted descriptively. Based on the results of data analysis, it can be concluded that the level of parental need for guidelines to train autistic children's communication at home is in the very high category.